2015
DOI: 10.1038/hr.2015.20
|View full text |Cite
|
Sign up to set email alerts
|

Decreased circulating anandamide levels in preeclampsia

Abstract: The endocannabinoid system has a key role in female reproduction, including implantation, decidualization and placentation. A growing number of studies indicate that placental and peripheral blood anandamide levels correlate closely with both spontaneous miscarriage and ectopic pregnancy. Anandamide has also been implicated in blood pressure regulation. In this study, we aimed to determine circulating anandamide levels in preeclampsia for the first time in the literature. Forty-three preeclamptic patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 52 publications
(51 reference statements)
2
13
1
Order By: Relevance
“…Our previous study [21,23] confirmed the value of measuring endothelial dysfunction along with arterial stiffness, which on some occasions were also linked to additional cardiovascular disorders. Immunological and inflammatory components are major underlying pathways leading to the development of PE, and some features of this disorder may become systemic later on [42][43][44]. This might also be the reason why low-dose aspirin is less effective in women with previous FGR compared to women with previous PE and may account for the lower efficacy of aspirin in preventing PE in women with chronic hypertension [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study [21,23] confirmed the value of measuring endothelial dysfunction along with arterial stiffness, which on some occasions were also linked to additional cardiovascular disorders. Immunological and inflammatory components are major underlying pathways leading to the development of PE, and some features of this disorder may become systemic later on [42][43][44]. This might also be the reason why low-dose aspirin is less effective in women with previous FGR compared to women with previous PE and may account for the lower efficacy of aspirin in preventing PE in women with chronic hypertension [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Another study published that CB1 expression was higher in placentas from pregnancies complicated by preeclampsia compared to controls, with no change in CB2 receptor levels (Fugedi, et al, 2014). Contradictory to these data is one study that demonstrated circulating levels of AEA are lower in preeclampsia (Molvarec et al, 2015). Blood AEA concentration, however, is not necessarily an indicator of local AEA concentration or AEA signaling within the placenta and may be under the control of feedback mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increased blood pressure in rats produces an elevation of AEA concentrations in the NTS (Seagard et al, 2004). On the other hand, circulating concentrations of AEA are significantly reduced in individuals with preeclampsia, a condition associated with hypertension in late pregnancy (Molvarec et al, 2015), suggesting that increased blood pressure alone is not sufficient to elevate circulating AEA concentrations.…”
Section: Circulating Endocannabinoids and Chronic Sns Or Hpa Axis Actmentioning
confidence: 99%